THERMAL SENSATION IN URBAN ENVIRONMENT The OPEN SKY CITY CUIABÁ-MT - Callejas, Ivan Julio Apolonio; Nogueira, Marta Crista de Jesus Albuquerque (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707701 The weather conditions of the urban climate influence the thermal sensation ofpedestrians moving in open environments. Thus, the meteorological variables play an importantrole for the quality life of the people who use these spaces, especially in cities Tropical ContinentalClimate. Thus, this study aimed to map the thermal sensation of walking under open condition inthe city of Cuiabá, MT, taking into consideration only the weather triggered by climate. Weremeasured weather variables and used to index Physiological Equivalent Temperature (PET) forevaluating the thermal sensation. During the daytime period, thermal comfort in the open has not been achieved in any month of the year in the city of Cuiabá-MT. The month of September wascharacterized as a month of higher relative frequency of hours with thermal discomfort withfeelings ranging from "slightly warm" to "extremely hot" on the scale proposed by Matzarakis andMayer, and "comfortable" to "very hot" in the proposal by Monteiro and Alucci. Moreover, themonth of June had the greatest number of hours of thermal comfort, with sensation ranging from"slightly cold" to "hot" on the scale proposed by Matzarakis and Mayer, and "ligeirmante cold" to"hot" on the scale proposed by Monteiro and Alucci. The results show how users are subjectdisconfortáveis of urban spaces in the city of Cuiaba-MT, which demonstrates the importance ofplanning these spaces, as well as the need to promote shading, whether or artificial tree, spaceswith high frequency of use.